KEPUTUSAN PEMBELIAN MELALUI SITUS BELANJA ONLINE TERHADAP PERILAKU KONSUMTIF MASYARAKAT DALAM PERSPEKTIF EKONOMI ISLAM - Muhammad Ridwan (FEBI IAIN Langsa, 2018)
This study aims to determine the relationship between purchasing decisions, products, prices, services, risks to consumer consumption behavior in the Islamic economic perspective (case study on Lazada Application Users in Medan). The method used is a quantitative approach using multiple linear regression analysis, supported by statistical tests, using the SPSS version 20. Testing partially coefficient of purchase decisions there is a relationship to consumptive behavior of 2.013 or 20.13%. The product coefficient has a relationship to consumptive behavior of 2,137 or 21,37%. The price coefficient is related to consumptive behavior of -2.637 or -26.37%. The service coefficient has a relationship to consumptive behavior of 2,893 or 28,93%. The risk coefficient is related to consumptive behavior of 2.043 or 20.43%. Partially there is a relationship between purchasing decisions, products, prices, services and risks to consumer behavior.